2017
DOI: 10.1093/gastro/gox014
|View full text |Cite
|
Sign up to set email alerts
|

Portal vein thrombosis in patients with cirrhosis

Abstract: Portal vein thrombosis (PVT) is frequent in patients with liver cirrhosis and possible severe complications such as mesenteric ischemia are rare, but can be life-threatening. However, different aspects of clinical relevance, diagnosis and management of PVT are still areas of uncertainty and investigation in international guidelines. In this article, we elaborate on PVT classification, geographical differences in clinical presentation and standards of diagnosis, and briefly on the current pathophysiological un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 73 publications
0
29
0
1
Order By: Relevance
“…More than two-thirds of cirrhosis patients with PVT have some evidence of inherited thrombophilia [14]. Prothrombin (PT) gene 20210A mutation is associated with a more than five-fold increased risk of developing PVT [15].…”
Section: Discussionmentioning
confidence: 99%
“…More than two-thirds of cirrhosis patients with PVT have some evidence of inherited thrombophilia [14]. Prothrombin (PT) gene 20210A mutation is associated with a more than five-fold increased risk of developing PVT [15].…”
Section: Discussionmentioning
confidence: 99%
“…Although this meta-analysis excluded neoplasms and inflammatory conditions to avoid heterogeneity and selection bias, previous research studies have also found these conditions to be independent risk factors for patients with cirrhosis without inherited thrombophilias to develop PVT. 27 Whether patients with tumoral PVT have an increased rate of inherited thrombophilias remains unclear and is an interesting avenue for future study. In general, data on inherited thrombophilia and risk of PVT in malignancy are limited;…”
Section: Ta B L E 2 (Continued)mentioning
confidence: 99%
“… 87 PVT prophylaxis may be indicated in cirrhotic patients awaiting LT or after hepatic resection. 117 …”
Section: Perioperative Antithrombotic Managementmentioning
confidence: 99%